use of ampicillin Sodium injection in the management of cervical dystocia and shortening of labor - Bantia , Mercy (Student’s Journal of Health Research Africa, 2023)
<div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 417.063px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.908941);">The article examined <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 293.833px; top: 417.063px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.93123);">the use of ampicillin <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 462.683px; top: 417.063px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.913046);">sodium <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 526.683px; top: 417.063px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.9162);">injection in the management of cervical <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 451.663px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.911444);">dystocia and shortening of labor. It arose from a qualitative observation and experimental survey. <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 486.063px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.90755);">Data was gathered from ten midwives <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 428.883px; top: 486.063px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.93575);">working in labor suite <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 609.917px; top: 486.063px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.911261);">and experimented on an infinite <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 520.663px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.918973);">number of mothers in activ <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 336.683px; top: 520.663px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.910597);">e labor. <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 401.483px; top: 520.663px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.899881);">Data was analyzed in a descriptive manner. <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 753.767px; top: 520.663px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.881415);">The data revealed <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 555.061px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.93035);">that for mothers with low parity in active labor with cervical dystocia due to early “pushing”, one <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 589.663px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.92323);">gram (1g) of injectable ampicillin given bolus commenced effacement and dilatation wit <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 828.367px; top: 589.663px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.899297);">h <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 624.063px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.918257);">shortened length of labor .In grand multiparous mothers in active labor, a maximum of two <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 658.663px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.928184);">grams (2g) of ampicillin injection given bolus yielded even faster cervical dilatation resulting in <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 693.097px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.912504);">shortened duration of labor. <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 347.283px; top: 693.097px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.914262);">However, the study could not reveal <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 642.117px; top: 693.097px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.908903);">the mechanism through which <div style="padding: 0px; margin: 0px; color: transparent; position: absolute; white-space: pre; cursor: text; transform-origin: 0% 0%; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; left: 120.04px; top: 727.697px; font-size: 20px; font-family: sans-serif; transform: scaleX(0.912419);">ampicillin sodium injection yielded the results hence need for more studies